Factors Influencing Employee’s Happiness at work - Ishaq, Abdulyekeen (2017)
This study titled “Factors influencing Employee’s happiness at work” was aimed at investigating and exploring some of the factors influencing employee’s happiness at work. For the purpose of this study, data were randomly collected via survey from 205 employees working in different Nigerian industries. The data were analyzed using IBM’s SPSS version 20. The findings of this study revealed that Income, Employment status, Work activities, Friendship and Leader-Employee relationship are positively related to employee’s happiness at work; specifically, Work activities and Leader-employee relationship exhibit largest direct positive significant influence on Employee’s happiness among all factors included in the study. The implications of the findings and the limitations of the study were sufficiently discussed and as comfortably as the relevant suggestions for future research.